Identification, release and olfactory detection of bile salts in the intestinal fluid of the Senegalese sole (Solea senegalensis) - Barata, Eduardo N. (2009)
Olfactory sensitivity to bile salts is wide-spread in teleosts; however, which bile salts are released in sufficient quantities to be detected is unclear. The current study identified bile salts in the intestinal and bile fluids of Solea senegalensis by mass spectrometry–liquid chromatography and assessed their olfactory potency by the electro-olfactogram. The main bile salts identified in the bile were taurocholic acid (342 mM) and taurolithocholic acid (271 mM) plus a third, unidentified, bile salt of 532.3 Da. These three were also present in the intestinal fluid (taurocholic acid, 4.13 mM; taurolithocholic acid, 0.4 mM). In sole-conditioned water, only taurocholic acid (0.31 μM) was released in sufficient quantities to be measured (release rate: 24 nmol.kg−1.min−1). Sole had high olfactory sensitivity to taurocholic acid but not to taurolithocholic acid. Furthermore, olfactory sensitivity was higher in the upper (right) olfactory epithelium than the lower (left). These two bile acids contribute about 40% of the olfactory potency of intestinal fluid and account for the difference in potency at the two epithelia. Taurocholic acid (but not taurolithocholic acid), and possibly other types of bile acid not tested, could be used as chemical signals and the upper olfactory epithelium is specialised for their detection.